EKONOMI ISLAM DALAM PERSPEKTIF SEJARAH - A. Muhyiddin Khotib Muhyiddin; Makhshushy Zakiyah (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2025)
Islamic economics has a long history that began during the time of Prophet Muhammad SAW and has continued to develop into the modern era. The fundamental principles of Islamic economics, such as social justice, equitable wealth distribution, and resource management based on ethical sharia, form the foundation of a sustainable and just economic system. This study aims to examine the development of Islamic economics from a historical perspective and its relevance in the modern era. The research method used is a qualitative descriptive approach with literature studies as the primary data source. The analysis focuses on literature discussing the history of Islamic economics, the application of Islamic economic principles, and the challenges faced during the colonial period and the era of globalization. The findings show that Islamic economics made significant contributions during the Islamic golden age through institutions such as zakat, waqf, and Islamic banking, which supported social welfare and economic equity. Despite facing significant challenges during colonial and modern periods, Islamic economics remains relevant with the development of sharia financial institutions offering alternatives to conventional financial systems. The contribution of this study is to deepen the understanding of Islamic economics and demonstrate its potential application in addressing global economic issues. This study also notes limitations in empirical data collection, thus further research is needed to examine the implementation of Islamic economics in various countries with different contexts.